2007
DOI: 10.1074/jbc.m608310200
|View full text |Cite|
|
Sign up to set email alerts
|

Activation of Protein Phosphatase 2A by Palmitate Inhibits AMP-activated Protein Kinase

Abstract: Evidence accumulated over the past several years indicates that the AMP-activated protein kinase (AMPK) 2 may be a therapeutic target for treating insulin resistance and type 2 diabetes (1). AMPK is a heterotrimeric protein formed by an ␣ subunit, which contains the catalytic activity, and by the ␤ and ␥ regulatory subunits important in maintaining stability of the heterotrimer complex (2). AMPK belongs to a family of energy-sensing enzymes functioning as a "fuel gauge" that monitors changes in the energy stat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

14
223
1
2

Year Published

2008
2008
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 250 publications
(240 citation statements)
references
References 49 publications
14
223
1
2
Order By: Relevance
“…As far as we know, this is the first observation that lithium affects phosphorylation levels of AMPK. It has been reported that lithium inhibits PP2A activity [20,21], which has been shown to regulate phosphorylation of AMPK [31]. The observed effects of lithium on AMPK may also be related to the neuroprotective effects of lithium because AMPK activation is connected to cell survival in several systems [32][33][34].…”
Section: Discussionmentioning
confidence: 98%
“…As far as we know, this is the first observation that lithium affects phosphorylation levels of AMPK. It has been reported that lithium inhibits PP2A activity [20,21], which has been shown to regulate phosphorylation of AMPK [31]. The observed effects of lithium on AMPK may also be related to the neuroprotective effects of lithium because AMPK activation is connected to cell survival in several systems [32][33][34].…”
Section: Discussionmentioning
confidence: 98%
“…The other mechanism is the inhibition of AMPK dephosphorylation by protein phosphatases [25,30] . In cell-free systems, protein phosphatase-2A and protein phosphatase-2C (PP2A/PP2C) dephosphorylate AMPK at Thr172 after binding to the threonine residue of AMPK, and AMP could inhibit this reaction by preventing this binding, which could increase the activity of AMPK [25,30,31] . Therefore, AMP activates AMPK by causing allosteric activation of AMPK as well as by making AMPK a Here, we showed that APS increased the cellular AMP levels and the AMP:ATP ratio in L6 myotubes, which may provide a mechanistic explanation for the activation of AMPK by APS.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, saturated fatty acids, which may accumulate in livers of fructose-fed rats due to the increased synthesis and reduced oxidation, activate PP2A. 39 PP2A activity has also been implicated in repression of PPAR␣ gene expression, 40 and inhibition of Akt and AMPK activities. [39][40][41] All these effects could increase the hepatic metabolic derangements induced by fructose.…”
Section: Discussionmentioning
confidence: 99%
“…39 PP2A activity has also been implicated in repression of PPAR␣ gene expression, 40 and inhibition of Akt and AMPK activities. [39][40][41] All these effects could increase the hepatic metabolic derangements induced by fructose. The fact that fructose is mainly metabolized in liver, while glucose is distributed to and metabolized in other body tissues, can explain why, despite also being metabolized to xylulose-5-phosphate, 30 glucose does not induce hyperleptinemia and hepatic leptin resistance when ingested at an equivalent amount of energy as fructose.…”
Section: Discussionmentioning
confidence: 99%